Left subclavian artery management in frozen elephant trunk: A novel technique. Issue 1 (14th October 2020) - Velayudhan, Bashi; Bashir, Mohamad; Idhrees, Mohammed
Abstract: Proximilization of frozen elephant trunk (FET) necessitates the ligation and reimplantation of the left subclavian artery (LSA), the origin of which is distal and posterior, make rerouting difficult and cumbersome. We describe a rather simple technique for subclavian artery exposure and effective anatomical reconstruction in the mediastinum coupled with hybrid FET utilization for aortic aneurysm in elective and nonelective settings. The division of the sternocleidomastoid coupled with the sandbag behind the left shoulder brings the LSA superficial enabling anastomosis without any difficulty.